Razumevanje transformacije vojne v 21. stoletju - Vuk, Pavel (Teorija in praksa, 2018)
This article critically discusses the understanding of the nature and causes of wars and, based on trend analysis, determines the intensity and most characteristic appearance of armed conflicts according to the types of war in the modern security environment. The question of whether the new wars are truly new brings to the forefront a diversity of perceptions of contemporary violence in the sociological and anthropological sense, since these wars can be described as a mixture of war, crime and human rights violations whose actors are both society and individuals. The fundamental reversal in the understanding and search for the causes of "new" wars and the way to exclude the "old" assumptions about the nature of war can also be attributed to the continuity of expert debates and the profession itself creating the basis for new methodologies of sociological research. Constant reflection on war, as one of the essential activities of man throughout his entire history, is also important for the perception of the changing nature and characteristics of modern warfare from the point of view of creating the possibility of lasting peace.
Keywords: Teorija vojne; Theory of war; Vojna; War